Hubungan Antara Pengetahuan, Pendapatan Ekonomi Dan Budaya Dengan Pernikahan Dini Pada Remaja Di Desa Sukaraja Kabupaten Bogor Tahun 2023 - Desi Arinia Rukiyah; Fitrya Ayu Anggraini; Indah Sri Wahyuni (Politeknik Karya Husada, 2024)
The relationship between knowledge, economic income and culture and early marriage among teenagers in Sukaraja Village, Bogor Regency in 2023. Early marriage is a marriage between a man and a woman, both of whom are under the minimum age regulated by law. invite. According to the Child Protection Law, chapter 1, article 1 paragraph (1), what is meant by early age is someone who is not yet 18 (eighteen) years old. The above limitation confirms that children at an early age are part of adolescence. The aim of this research is to determine the factors related to the incidence of early marriage among teenagers in Sukaraja Village, Bogor Regency in 2023. This type of research is analytical descriptive with primary data. This research design uses